Recommendations and Extraction of Clinical Variables of Pediatric Multiple Sclerosis Using Common Data Elements. Issue 3 (June 2018) - Newland, Pamela; Newland, John M.; Hendricks-Ferguson, Verna L.; Smith, Judith M.; Oliver, Brant J.
Abstract : ABSTRACT: Purpose: The purpose of this article was to demonstrate the feasibility of using common data elements (CDEs) to search for information on the pediatric patient with multiple sclerosis (MS) and provide recommendations for future quality improvement and research in the use of CDEs for pediatric MS symptom management strategiesMethods: The St. Louis Children's Hospital (SLCH), Washington University (WU) pediatrics data network was evaluated for use of CDEs identified from a database to identify variables in pediatric MS, including the key clinical features from the disease course of MS. The algorithms used were based on International Classification of Diseases, Ninth/Tenth Revision, codes and text keywords to identify pediatric patients with MS from a de-identified database. Data from a coordinating center of SLCH/WU pediatrics data network, which houses inpatient and outpatient records consisting of patients (N = 498 000), were identified, and detailed information regarding the clinical course of MS were located from the text of the medical records, including medications, presence of oligoclonal bands, year of diagnosis, and diagnosis code.Results: There were 466 pediatric patients with MS, with a few also having the comorbid diagnosis of anxiety and depression.Conclusions: St. Louis Children's Hospital/WU pediatrics data network is one of the largest databases in the United States of detailed data, with the ability to query and validate clinical data for research on MS. Nurses and other healthcare professionals working with pediatric MS patients will benefit from having common disease identifiers for quality improvement, research, and practice. The increased knowledge of big data from SLCH/WU pediatrics data network has the potential to provide information for intervention and decision-making that can be personalized to the pediatric MS patient.